Combination of First Derivative Spectrophotometry and H-Point Standard Addition Method for Simultaneous Determination of Guaifenesin and Theophylline in Cough Syrup - R. Hajian; N. Shams; Z. Davarpanah (E-Journal of Chemistry)
Combination of first derivative spectrophotometric and H-point standard addition method (HPSAM) has been applied for simultaneous determination of guaifenesin and theophylline. First derivative signals at the two pairs of wavelengths, 282.0-290.2 nm and 277.4-287.8 nm were monitored with the addition of standard solutions of both guaifenesin and theophylline in the ratio of 1:1. The method is able to accurately determine guaifenesin and theophylline (1:5 to 10:1) mole ratios. Accuracy and reproducibility of the determination method on the various amounts of guaifenesin and theophylline with known concentrations were evaluated in their binary mixtures. The recommended procedure was successfully applied to some cough syrups and synthetic mixtures with satisfactory results.